2010
DOI: 10.1002/hbm.20909
|View full text |Cite
|
Sign up to set email alerts
|

Altered representation of expected value in the orbitofrontal cortex in mania

Abstract: The observed alterations are consistent with a state-related affective processing bias during the expectation of gains and losses which may contribute to clinical features of mania, such as the enhanced motivation for seeking rewards and the underestimation of risks and potential punishments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
95
3
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(110 citation statements)
references
References 65 publications
10
95
3
1
Order By: Relevance
“…Manic behavior consists in part of impairment in these domains, with patients displaying exaggerated reward-seeking behaviors and overoptimistically assessing the outcomes of their actions. It is unclear what relative roles the NA, striatum and orbitofrontal cortex (OFC) might play in mania: stimulation at the NA has been observed to produce euphoria [31] , the striatum has been tied to the experience of pleasure [29] and fMRI data suggest that OFC abnormalities can be present in patients with mania during expected-gain tasks [32] . There is some evidence that ALIC-NA DBS modulates these circuits: high-frequency stimulation of the NA has been shown to inhibit the firing of OFC neurons in rats [33] and intraoperative ventral ALIC-NA stimulation has been found to acutely elevate mood [31] .…”
Section: Discussionmentioning
confidence: 99%
“…Manic behavior consists in part of impairment in these domains, with patients displaying exaggerated reward-seeking behaviors and overoptimistically assessing the outcomes of their actions. It is unclear what relative roles the NA, striatum and orbitofrontal cortex (OFC) might play in mania: stimulation at the NA has been observed to produce euphoria [31] , the striatum has been tied to the experience of pleasure [29] and fMRI data suggest that OFC abnormalities can be present in patients with mania during expected-gain tasks [32] . There is some evidence that ALIC-NA DBS modulates these circuits: high-frequency stimulation of the NA has been shown to inhibit the firing of OFC neurons in rats [33] and intraoperative ventral ALIC-NA stimulation has been found to acutely elevate mood [31] .…”
Section: Discussionmentioning
confidence: 99%
“…2a .) This type of non-reward or punishment-related responsiveness has been found to be very different in mania, with apparently decreasing activations in the lateral orbitofrontal cortex during expectation of increasing loss (Bermpohl et al, 2010), the opposite of what is found in healthy participants (Grabenhorst and Rolls, 2011;O'Doherty et al, 2001). In this context, of potentially reduced sensitivity or even abnormal function of the lateral orbitofrontal cortex non-reward system in mania, it is relevant that manic bipolar patients continue to pursue immediate rewards despite negative consequences (Wessa et al, 2014).…”
Section: Mania and Bipolar Disordermentioning
confidence: 99%
“…It is likely that our sample size (n ¼ 20 per group) was insufficiently powered to detect diagnostic effects during these phases using this type of multi-level model. Therefore, future studies comparing cases and controls using larger sample sizes and/or tasks with more trials per event type to assess magnitude-related factors such as expected value encoding are needed to assess these factors in unmedicated BD (Bermpohl et al, 2010).…”
Section: Whole-brain Findingsmentioning
confidence: 99%